Principal's Strategy in Implementing a Culture of Quality in Elementary School: A Perspective of David Hunger and Wheelen - Haya Nabila; Makherus Sholeh; Ethem Gürhan (Institut Agama Islam Negeri Lhokseumawe, 2025)
This study is situated within the broader discourse on educational quality culture and strategic leadership, particularly in faith-based schooling contexts where institutional effectiveness is closely linked to value internalization and stakeholder alignment. This study aims to examine principals’ strategic management processes in implementing and sustaining quality culture in Islamic elementary schools. A qualitative multi-case study design was employed involving semi-structured interviews, non-participant observations, and document analysis, analyzed using an interactive data analysis model consisting of data condensation, data display, and conclusion drawing. Quality culture development operates through an integrated strategic cycle encompassing environmental scanning, participatory planning, value-based implementation, and reflective evaluation. Applications of this study: The findings are applicable to educational leadership, school management, quality assurance systems, and faith-based education development. The study integrates the Hunger and Wheelen strategic management framework with Islamic value institutionalization processes, producing an empirically grounded strategic leadership model for supporting quality culture development. Sustainable quality culture in Islamic elementary education is achieved through cyclical strategic alignment integrating institutional diagnostics, stakeholder engagement, ritualized character habituation, and developmental supervision systems.